Structure and Function of Major SARS-CoV-2 and SARS-CoV Proteins - Ritesh Gorkhali; Prashanna Koirala; Sadikshya Rijal; Ashmita Mainali; Adesh Baral; Hitesh Kumar Bhattarai (Bioinformatics and Biology Insights, 2021)
SARS-CoV-2 virus, the causative agent of COVID-19 pandemic, has a genomic organization consisting of 16 nonstructural proteins (nsps), 4 structural proteins, and 9 accessory proteins. Relative of SARS-CoV-2, SARS-CoV, has genomic organization, which is very similar. In this article, the function and structure of the proteins of SARS-CoV-2 and SARS-CoV are described in great detail. The nsps are expressed as a single or two polyproteins, which are then cleaved into individual proteins using two proteases of the virus, a chymotrypsin-like protease and a papain-like protease. The released proteins serve as centers of virus replication and transcription. Some of these nsps modulate the host’s translation and immune systems, while others help the virus evade the host immune system. Some of the nsps help form replication-transcription complex at double-membrane vesicles. Others, including one RNA-dependent RNA polymerase and one exonuclease, help in the polymerization of newly synthesized RNA of the virus and help minimize the mutation rate by proofreading. After synthesis of the viral RNA, it gets capped. The capping consists of adding GMP and a methylation mark, called cap 0 and additionally adding a methyl group to the terminal ribose called cap1. Capping is accomplished with the help of a helicase, which also helps remove a phosphate, two methyltransferases, and a scaffolding factor. Among the structural proteins, S protein forms the receptor of the virus, which latches on the angiotensin-converting enzyme 2 receptor of the host and N protein binds and protects the genomic RNA of the virus. The accessory proteins found in these viruses are small proteins with immune modulatory roles. Besides functions of these proteins, solved X-ray and cryogenic electron microscopy structures related to the function of the proteins along with comparisons to other coronavirus homologs have been described in the article. Finally, the rate of mutation of SARS-CoV-2 residues of the proteome during the 2020 pandemic has been described. Some proteins are mutated more often than other proteins, but the significance of these mutation rates is not fully understood.